Acute aortic syndromes and aortic emergencies - Baliyan, Vinit; Parakh, Anushri; Prabhakar, Anand M.; Hedgire, Sandeep (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2018)
Acute aortic syndrome (AAS) and emergencies are relatively uncommon but are considered as life threatening, potentially fatal conditions. Different forms of aortic emergencies/AAS are often clinically indiscernible. Prompt and accurate diagnosis of these entities significantly influences prognosis and guides therapy. We aim to elucidate the pertinent role that radiology plays in the management of acute aortic diseases, with contrast-enhanced computed tomography angiography (CTA) being the most rapid and robust imaging technique.